Culex siphanulatus, a new species of mosquito from the coast of Rio de Janeiro State, Brazil (Diptera: Culicidae) - Ricardo Lourenco-de-Oliveira (Memórias do Instituto Oswaldo Cruz., 1987)
Culex siphanulatus, sp. n. is described from specimens collected in bromeliads of the coast of Rio de Janeiro State, Brazil. The description includes illustrations of female, male genitalia and chaetotaxy of pupa and larva. This species is easily distinguished from the others of subgenus Microculex and does not belong to any of the four series proposed for the grouping of its species. Culex siphanulatus sp. n. é descrito de espécimes coletados em bromélias do Estado do Rio de Janeiro. A descrição inclui ilustrações do aldulto fêmea, da genitália masculina e da quetotaxia da pupa e da larva. Esta espécie é facilmente distinguida das demais do subgênero Microculex e não pertence a qualquer das quatro séries propostas para agrupar as espécies deste subgênero.